Sosialisasi dan Demonstrasi Pemberian Vitamin B Kompleks untuk Kambing di Peternakan Ashar Farm Kota Payakumbuh - Kadran Fajrona; Ferawati Ferawati; Linda Suhartati; El Latifa Sri Suharto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Ashar Farm is a goat farming business in Balai Cacang Village, North Payakumbuh District, Payakumbuh City, West Sumatra, Indonesia. It was established in 2020 with a starting population of 30 goats. An intensive maintenance system has been applied. The condition of the farm is currently experiencing a population decline; as many as 17 goats are kept. The population decline is due to a lack of appetite for livestock, resulting in death. So far, the farmer provides only forage without adding appetite-enhancing supplements such as vitamin B complex as animal feeding. It assumes that there needs to be more nutrition for the goats. On the other hand, a Vitamin B complex can increase livestock productivity—the community engagement activity aimed to provide knowledge and skills of breeders about administering Vitamin B complex. The method of this activity was carried out by socialization and demonstrations using the Vitamin B complex as an additive in feed. As a result of this activity, Ashar Farm farmers gain new knowledge to overcome the lack of appetite for livestock and how to inject vitamin B complex into the goats so that their livestock business can be more productive.